The Letters of Wilkie Collins
XIII, 348 p.
Keywords: Wilkie Collins is the only leading Victorian novelist whose letters have not been published. This two-volume edition, edited by William Baker and William Clarke, fills a gaping hole in any assessment of one of the nineteenth century's most loved novelists. It is also extremely timely. Two recent biographies have re-assessed his private life and his literary achievements. His best-known novels, The Women in White and The Moonstone, continue to feature on television, and most of his thirty-odd novels are still in print. This authorised edition reproduces his selection of around 700 key letters of the 2,000 known to be in existence, some recently discovered. Summaries and sources of the remaining letters are provided in an appendix.